Evaluation of linolenic acid supplementation in extender for freezability and fertility of Murrah buffalo (Bubalus bubalis) bull semen - SINGH, S; SINGH, A K; CHEEMA, R S; KUMAR, A; DHINDSA, S S; GANDOTRA, V K; SINGH, P (The Indian Journal of Animal Sciences, 2019)
Linolenic acid is integral component of cell membrane that has the ability to protect the structural and functional integrity of buffalo spermatozoa during freeze-thawing. Therefore, present study was designed to evaluate supplementation of linolenic acid (0, 2.5, 5, 7.5 and 10.0 ng/ml) in extender on freezability and in vivo fertility of buffalo bull spermatozoa. Semen from healthy breeding Murrah buffalo bulls (4) was collected using artificial vagina (one ejaculate/bull/session; n=24). Qualified semen ejaculates (1–2 ml volume; >70% motility; ≥4 mass activity; 1.0 billion/ml concentration) were diluted with Tris-citric acid extender containing 0.0 (control), 2.5, 5.0, 7.5 and 10.0 ng/ml linolenic acid at 37°C and cryopreserved following established protocol. Sperm progressive motility, viability and plasma membrane integrity were recorded higher in extender containing 5.0 ng/ml of linolenic acid compared to control and other concentrations. Sperm acrosome and DNA integrity exhibited no difference in all experimental extenders with linolenic acid compared to control. Total 60 artificial inseminations were performed with the best evolved extender having linolenic acid (5.0 ng/ml) and control (30 inseminations each). In vivo fertility rates of buffalo semen were recorded higher with extender containing linolenic acid (5.0 ng/ml; 46.7%) compared to control (36.7%). In conclusion, supplementing 5.0 ng/ml linolenic acid in extender improved the postthaw quality and in vivo fertility of cryopreserved Murrah buffalo bull semen.